Clinicopathologic Significance of CXCL12 and CXCR4 Expressions in Patients with Colorectal Cancer - Naomi Yoshuantari; Didik Setyo Heriyanto; Susanna Hilda Hutajulu; Johan Kurnianda; Ahmad Ghozali (Gastroenterology Research and Practice)
Background. Colorectal cancer (CRC) is both a global and national burden, being the third most common malignancy in men and the second in women, worldwide. The prognosis of CRC is affected by various factors like the histological grade, angiolymphatic invasion, and distant metastases. Metastasis is an intricate process; one of the possible mechanisms is through the interaction of the chemokines CXCL12 and CXCR4. This study aims to reveal the expression patterns of CXCL12 and CXCR4 in CRC. Methods. The quantitative expressions of CXCL12 and CXCR4 messenger RNA (mRNA) were evaluated in 32 patients with adenocarcinoma-type CRC. Real-time polymerase chain reaction (qRT-PCR) was performed on formalin-fixed tissues. CXCL12 and CXCR4’s expressions, clinicopathologic features, and the treatment response to the CRC were analysed. Results. All tumour tissues showed higher levels of both chemokines compared to normal colonic tissue. The expression of CXCL12 mRNA was higher in rectal location (p=0.04) with a tendency to be higher in later stages (p=0.15), while the expression of CXCR4 was lower in tumours with a lymphatic invasion (p=0.02), compared to their counterparts. There was no difference in the expression of CXCL12 and CXCR4 according to the patients’ ages, gender, tumour differentiation, or response to chemotherapy. Conclusion. Our study demonstrated that the mRNA expression of CXCL12 was significantly correlated with rectal location. CXCR4 mRNA expression was inversely correlated in tumours with a lymphatic invasion.